2018
DOI: 10.3389/fphar.2018.00646
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Emodin and Efflux Transporters on Rat Enterocyte by a Validated Ussing Chamber Technique

Abstract: Emodin, a major active anthraquinone, frequently interacts with other drugs. As changes of efflux transporters on intestine are one of the essential reasons why the drugs interact with each other, a validated Ussing chamber technique was established to detect the interactions between emodin and efflux transporters, including P-glycoprotein (P-gp), multidrug-resistant associated protein 2 (MRP2), and multidrug-resistant associated protein 3 (MRP3). Digoxin, pravastatin, and teniposide were selected as the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…As is well known, three key processes are generally involved in transcytosis of the nanoparticles: endocytosis at AP side, intracellular transport through cytoplasm, and exocytosis at BL side. As for the intestinal absorption of bile acid in which ASBT, IBABP, OSTα-OSTβ, and MRP3 play a programmable mediation role, an analogous situation was also expected for the transcytosis of DA-conjugated micelles via mediation of these transporters. To examine this issue, three inhibitors of the bile acid transporters were selected to pretreat the monolayer to assess their effect on the transcellular transport of the micelles.…”
Section: Results and Discussionmentioning
confidence: 91%
“…As is well known, three key processes are generally involved in transcytosis of the nanoparticles: endocytosis at AP side, intracellular transport through cytoplasm, and exocytosis at BL side. As for the intestinal absorption of bile acid in which ASBT, IBABP, OSTα-OSTβ, and MRP3 play a programmable mediation role, an analogous situation was also expected for the transcytosis of DA-conjugated micelles via mediation of these transporters. To examine this issue, three inhibitors of the bile acid transporters were selected to pretreat the monolayer to assess their effect on the transcellular transport of the micelles.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Ostensibly harmless natural products—such as juices, fruits, vegetables and herbal products in the form of ayurvedic medicine—have been reported in several studies to potentially cause many drug interactions affecting drug absorption mediated by transporters [ 41 , 42 ]. For example, emodin—a potential antineoplastic drug and a major component of the Rhamnus, Rumex, Aloe , Rheum and Cassia species—has been reported to be a possible P -gp inducer [ 26 ] or an inhibitor [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies concerning drug interactions with herbal medicines involving both P -gp and OATP1A2. Furthermore, it has been reported that the emodin acts on P -gp as an inducer [ 26 ] or an inhibitor [ 18 ]. Our results clarify the inhibitory effect of emodin on the P -gp through in vitro and in vivo study.…”
Section: Introductionmentioning
confidence: 99%
“…For P-gp, in order to investigate the effect of curcumin on its transport function, curcumin and RHO-123 were applied to K562/DOX cells simultaneously. Following incubation for 45 min, the intracellular RHO-123 levels were detected, with the P-gp-specific inhibitor VRP used as a positive control (47,48). The results suggested that when curcumin was applied to K562/DOX cells, the intracellular accumulation of RHO-123 increased significantly, indicating that curcumin inhibited the function of P-gp.…”
Section: Discussionmentioning
confidence: 99%